ANALISIS PENGARUH FAKTOR MAKRO dan MIKRO EKONOMI TERHADAP RETURN SAHAM SEKTOR PERBANKAN di BURSA EFEK INDONESIA TAHUN 2010-2014 - Simanjuntak, Trisha Bethania (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aim is to determine the effect of macro factors, namely inflation and interest rates on deposits and micro factors that Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Total Assets Turnover ( TATO), Earnings per Share (EPS ) to the stock return of the banking sector in Indonesia stock Exchange in 2010-2014. This study uses a panel regression methods and the sample used is 27 banking company that issued the complete annual financial statements in 2010-2014 were listed in the Indonesia Stock Exchange. Results from this study is jointly variable inflation, interest rates on deposits, CR, DER, ROA, ROE, TATO, EPS significant effect on stock returns of banking, while partial inflation significant positive effect on stock returns, interest rates on deposits negative effect significant to stock return, CR significant effect on stock returns, DER significant effect on stock returns, ROA significant negative effect on stock returns, ROE not significant effect on stock returns, TATO significant positive effect on stock returns and EPS not significant effect on stock returns. This research is expected to help the company to anticipate in maintaining the value of the company and provide information to the investor in making an investment decision.Keywords: Macro factors, micro factors, stock returns, the banking sector